Inorganic CsPbI3 Perovskite‐Based Solar Cells: A Choice for a Tandem Device. Issue 7 (19th June 2017) - Ahmad, Waqar; Khan, Jahangeer; Niu, Guangda; Tang, Jiang
Abstract : Hygroscopicity risk and organic–inorganic hybrid perovskites easy decomposition in solar cells limit their usefulness. Apart from the hybrid organic–inorganic perovskites, inorganic perovskite solar cells display a better stability toward moisture, light soaking, and thermal stressing. However, most inorganic perovskites are inappropriate for single junction or tandem solar cells due to their large bandgaps (>1.8 eV), which eventually results in light absorption loss. Fortunately, cubic CsPbI3 perovskite (having 1.73 eV bandgap) could potentially serve as top cells in tandem devices with silicon solar cells. Poor phase stability of CsPbI3 is considered a major obstacle to design CsPbI3 perovskite solar cells. This review highlights the most recent studies on the progress in CsPbI3 ‐based solar cell device field. Moreover, this review also summarizes certain strategies to improve phase stability, such as size reduction to nanocrystal or external cations/anions doping, with the aim to improve the devices design. Abstract : CsPbI3 is one of the best choices as the top cell in tandem devices with Si solar cells due to its appropriate bandgap (1.73 eV), inorganic skeleton and thus, potentially high stability. Possible strategies, such as size reduction to nanocrystal or external cations/anions doping, are summarized to design high performance and stable solar cells.